2023
DOI: 10.3390/ma16052098
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Duplex Surface Treatment on the Corrosion and Tribocorrosion Characteristics of Additively Manufactured Ti-6Al-4V

Abstract: The use of additively manufactured components specifically utilizing titanium alloys has seen rapid growth particularly in aerospace applications; however, the propensity for retained porosity, high(er) roughness finish, and detrimental tensile surface residual stresses are still a limiting factor curbing its expansion to other sectors such as maritime. The main aim of this investigation is to determine the effect of a duplex treatment, consisting of shot peening (SP) and a coating deposited by physical vapor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Furthermore, the friction coefficient was greatly reduced through duplex coatings during the tribocorrosion test due to the good resistance to seawater and the graphitization effect produced by the TiSiCN layer. Zammit et al [ 282 ] reported a two-phase treatment consisting of shot peening (SP) and physical vapor deposition (PVD) coatings to improve the surface properties of additive manufactured Ti-6Al-4V material. SP and duplex treatments resulted in a 13% and 210% increase in hardness, respectively.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…Furthermore, the friction coefficient was greatly reduced through duplex coatings during the tribocorrosion test due to the good resistance to seawater and the graphitization effect produced by the TiSiCN layer. Zammit et al [ 282 ] reported a two-phase treatment consisting of shot peening (SP) and physical vapor deposition (PVD) coatings to improve the surface properties of additive manufactured Ti-6Al-4V material. SP and duplex treatments resulted in a 13% and 210% increase in hardness, respectively.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…Traditional methods for surface enhancement, such as surface hardening [14] and surface cladding [13,14], have been utilized to improve their surface wear and erosion characteristics. In line with this, recent efforts have focused on advancing the surface properties of 3D-printed titanium components [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…Titanium alloys fulfill the need for lightweight, high-strength, and corrosion-resistant material for modern manufacturing. As a result, the demand for titanium alloy has been increasing in aerospace [ 1 , 2 ], marine [ 3 , 4 ], and biomedical fields [ 5 , 6 ]. During the service period of titanium alloy components under complex conditions, fatigue failure is one of the main reasons for inducing damage and fracture of the components, which could result in serious consequences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%